High resolution profiling of human exon methylation by liquid hybridization capture-based bisulfite sequencing - Wang, Junwen (BioMed Central, 2011)
BACKGROUND: DNA methylation plays important roles in gene regulation during both normal developmental and disease states. In the past decade, a number of methods have been developed and applied to characterize the genome-wide distribution of DNA methylation. Most of these methods endeavored to screen whole genome and turned to be enormously costly and time consuming for studies of the complex mammalian genome. Thus, they are not practical for researchers to study multiple clinical samples in biomarker research. RESULTS: Here, we display a novel strategy that relies on the selective capture of target regions by liquid hybridization followed by bisulfite conversion and deep sequencing, which is referred to as liquid hybridization capture-based bisulfite sequencing (LHC-BS). To estimate this method, we utilized about 2 μg of native genomic DNA from YanHuang (YH) whole blood samples and a mature dendritic cell (mDC) line, respectively, to evaluate their methylation statuses of target regions of exome. The results indicated that the LHC-BS system was able to cover more than 97% of the exome regions and detect their methylation statuses with acceptable allele dropouts. Most of the regions that couldn't provide accurate methylation information were distributed in chromosomes 6 and Y because of multiple mapping to those regions. The accuracy of this strategy was evaluated by pair-wise comparisons using the results from whole genome bisulfite sequencing and validated by bisulfite specific PCR sequencing. CONCLUSIONS: In the present study, we employed a liquid hybridisation capture system to enrich for exon regions and then combined with bisulfite sequencing to examine the methylation statuses for the first time. This technique is highly sensitive and flexible and can be applied to identify differentially methylated regions (DMRs) at specific genomic locations of interest, such as regulatory elements or promoters.